ANALYSIS ON PERFORMANCE SCALABILITY AVAILABILITY AND SECURITY IN VARIOUS CLOUD ENVIRONMENT SYSTEMS - KUMAR, ATHMAKURI NAVEEN (The journal of contemporary issues in business and government, 2021)
Cloud computing refers to the sharing of resources and computing tasks among a network of computers. Cloud computing enables us to do all of these things by utilising remote servers to transmit, store, and retrieve information. Because of the vast number of Virtual Machines available in the cloud, we now have the chance to perform parallel computations. The biggest threats to cloud computing may now come from its performance, scalability, availability, and security. In this article, we'll discuss the challenges of scalability, availability, and security in the context of cloud computing, and outline the steps we've taken to improve the safety and reliability of our infrastructure in this setting. Also, we stress cloud computing's elasticity. Also covered will be some of the key factors in achieving the promised high performance of cloud computing.